2003
DOI: 10.1021/la026247m
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Asphaltene Microenvironments Evidenced by Fluorescence Solvatochromism

Abstract: This work involved the study of Cold Lake asphaltenes' behavior in toluene and o-dichlorobenzene. The changes in asphaltene microenvironments with the increase in asphaltene concentration were observed using fluorescence solvatochromism. The reporter molecule chosen was the environmentally sensitive fluorophore PRODAN. This procedure represents a novel and sensitive method to study asphaltene solutions, and might bring additional information to the existent database of asphaltene properties.A pre-aggregation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 68 publications
2
20
0
Order By: Relevance
“…They interpreted the shift to occur at a critical aggregation concentration (CAC) (range 0.2-1.5 g/l) and suggested that the CAC was caused by the formation of larger asphaltene molecular aggregates from the smaller asphaltene molecular aggregates. The CAC values reported by Pietaru and Cramb [19] were close to the MCP values measured by Priyanto et al [18]. Both MCP and CAC, nevertheless, are close to CMC values reported in the literature.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…They interpreted the shift to occur at a critical aggregation concentration (CAC) (range 0.2-1.5 g/l) and suggested that the CAC was caused by the formation of larger asphaltene molecular aggregates from the smaller asphaltene molecular aggregates. The CAC values reported by Pietaru and Cramb [19] were close to the MCP values measured by Priyanto et al [18]. Both MCP and CAC, nevertheless, are close to CMC values reported in the literature.…”
Section: Introductionsupporting
confidence: 88%
“…It is believed that there is a change in the rate of aggregation at this point. In this study, henceforth, this point is called the critical aggregation concentration (CAC), the same terminology employed by Pietaru and Cramb [19]. The surface tension decreases observed were relatively small in the range of 36.1-35.5 mN/m.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…51,52 FL spectra of aromatic moieties are fundamentally related to the aromatic fluorophores' sizes and conjugation; the appearance of new bands, shifts in emission wavelengths and FL intensity have been correlated with changes surrounding these fluorophores, like the bathochromic red shifts caused by intermolecular aggregation. [53][54][55] One problem with asphaltenes is their color;…”
Section: Molecular Aggregationmentioning
confidence: 99%
“…That is, the fluorescence solvatochromism was observed in the nanocapsule. The fluorescence intensity depended on the polarity parameter [19] of the solvent as shown in Fig. 6b: 1697 RFU for ethanol (0.289), 1028 RFU for 2-propanol (0.273), and 925 RFU for DMSO (0.263).…”
Section: Solvatochromism Of the Fluorescent Molecules In The Interiormentioning
confidence: 96%